THE IMPORTANCE OF THERAPEUTIC RECREATION INTERVENTIONSIN RECREATION MANAGEMENT - Ozsu Nebioğlu, Ilbilge (Acta Scientiae et Intellectus, 2024)
In this review study, recreational applications that have effects on different components of health individually and socially, and therapeutic recreation applications that have a special application area under the roof of health recreation are included. The main purpose of the study is to draw attention to the importance of therapeutic recreation practices in recreation management. The difference between the concepts of recreational therapy and therapeutic recreation, which are close to each other, has been mentioned. The relationship between the concept of recreation management and health was discussed, and then the effects of recreational practices on health were examined and studies on the concept of therapeutic recreation and therapeutic recreation practices were discussed. Therapeutic recreation practices were analyzed by considering different groups and various health complaints. Therapeutic recreation practices are included in the prevention or treatment of the negative experiences of the individual and society under conditions that make life difficult and reduce the quality of life. The deficiencies and importance of therapeutic recreation practices in recreation management are mentioned. It is recommended that these practices be planned and systematically designed considering the needs of the individual and society in recreation management.